The Fundamental Institutions of China's Reforms and Development - Xu, Chenggang (Journal of Economic Literature, 2011)
China's economic reforms have resulted in spectacular growth and poverty reduction. However, China's institutions look ill-suited to achieve such a result, and they indeed suffer from serious shortcomings. To solve the “China puzzle,” this paper analyzes China's institution—a regionally decentralized authoritarian system. The central government has control over personnel, whereas subnational governments run the bulk of the economy; and they initiate, negotiate, implement, divert, and resist reforms, policies, rules, and laws. China's reform trajectories have been shaped by regional decentralization. Spectacular performance on the one hand and grave problems on the other hand are all determined by this governance structure. (JEL O17, O18, O43, P21, P25, P26)